2014
DOI: 10.1007/s00775-014-1148-z
|View full text |Cite
|
Sign up to set email alerts
|

Catecholase activity, DNA cleavage and cytotoxicity of six Zn(II) complexes synthesized from designed Mannich ligands: higher reactivity of mononuclear over dinuclear

Abstract: Six zinc(II) complexes have been synthesized from two designed Mannich-base ligands which consist of three dinuclear complex [Zn2(L(1))2X2] (1-3) and three mononuclear complex [ZnH(L(2))X2] (4-6), respectively, where X = Cl(-) (1,4), Br(-) (2,5), I(-) (3,6), as reported earlier by us (Sanyal et al., Inorg Chem 53:85-96, 2014). The catecholase activity of the complexes has been investigated under completely aerobic conditions in DMF-water medium (9:1) at pH 8.5 against the model substrate 3,5-di-tert-butylcatec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Moreover, Das et al proposed that the conversion of 3,5-DTBC to 3,5-DTBQ can be promoted by the redox-innocent Zn(II) ion via a radical pathway. 25 In this case, the coordinated ligand undergoes reduction with the concomitant oxidation of catechol to form semibenzoquinone.…”
Section: Catechol Oxidase Studies and Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Das et al proposed that the conversion of 3,5-DTBC to 3,5-DTBQ can be promoted by the redox-innocent Zn(II) ion via a radical pathway. 25 In this case, the coordinated ligand undergoes reduction with the concomitant oxidation of catechol to form semibenzoquinone.…”
Section: Catechol Oxidase Studies and Kineticsmentioning
confidence: 99%
“…22 Recent investigations have also shown that some manganese(II/III), nickel(II), zinc(II) and cobalt(II/III) species can also mediate such catechol oxidation. [23][24][25][26] It becomes evident that in the case of Ni(II) and Mn(III) metal-centered redox participation is most probably responsible for the catecholase activity of these model compounds whereas in the case of redox innocent Zn(II) this activity can be promoted through the generation of a ligand-centered radical. However, to the best of our knowledge, no mechanistic studies have yet been conducted on the catecholase-like activity of cobalt complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In this case g || is greater than g ⊥ which indicated that in solution the coordination geometry around the metal centre was probably square pyramidal . Addition of 3,5‐DTBC to the solution of complex 1 , an extra peak in EPR spectrum (near g ∼2) was observed which was probably due to the generation of ligand centred radical (shown in Figure S30).…”
Section: Resultsmentioning
confidence: 99%
“…[62][63][64][65][66] Now to rationalize the exact pathway for our complexes we have performed DFT calculation (vide infra). [62][63][64][65][66] Now to rationalize the exact pathway for our complexes we have performed DFT calculation (vide infra).…”
Section: Structural Characterization Reveals Thatmentioning
confidence: 99%